The Violence of the Masquerade: Law Dressed Up as Justice: Насилството на преправањето: Законот преоблечен во правда - Cornell, Drucilla; Stoev, Goran (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Drucilla Cornell | Друсила Корнел Title (English): The Violence of the Masquerade: Law Dressed Up as Justice Title (Macedonian): Насилството на преправањето: Законот преоблечен во правда Translated by (English to Macedonian): Goran Stoev | Горан Стоев Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 33-69 Page Count: 36 Citation (English): Drucilla Cornell, “The Violence of the Masquerade: Law Dressed Up as Justice,” Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004): 33-69. Citation (Macedonian): Друсила Корнел, „Насилството на преправањето: Законот преоблечен во правда“, превод од англиски Горан Стоев, Идентитети: списание за политика, род и култура, т. 3, бр. 2 (зима 2004): 33-69.